2004
DOI: 10.1007/s00429-004-0384-3
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampal continuation (indusium griseum): its connectivity in the hedgehog tenrec and its status within the hippocampal formation of higher vertebrates

Abstract: The indusium griseum and its precallosal extension are usually considered poorly differentiated portions of the hippocampus. The connections of this so-called 'hippocampal continuation' (HCt) have only been analyzed so far in rodents, which show one of the least-developed HCt among mammals. In this study we have investigated the relatively well differentiated HCt of the small Madagascan hedgehog tenrec (Afrotheria) using histochemical and axonal transport techniques. The tenrec's HCt shows associative and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 121 publications
(145 reference statements)
1
28
0
Order By: Relevance
“…The function of the indusium griseum remains unclear. Tract-tracing studies indicate that, in rats and mice (Wyss and Sripanidkulchai, 1983;Adamek et al, 1984), and to a lesser extent in Madagascan hedgehogs (Kunzle, 2004), the indusium griseum receives direct projections from the main olfactory bulb. In hedgehogs, efferents of the indusium griseum reach, among other sites, the minor islands of Calleja (Kunzle, 2004).…”
Section: Indusium Griseummentioning
confidence: 99%
“…The function of the indusium griseum remains unclear. Tract-tracing studies indicate that, in rats and mice (Wyss and Sripanidkulchai, 1983;Adamek et al, 1984), and to a lesser extent in Madagascan hedgehogs (Kunzle, 2004), the indusium griseum receives direct projections from the main olfactory bulb. In hedgehogs, efferents of the indusium griseum reach, among other sites, the minor islands of Calleja (Kunzle, 2004).…”
Section: Indusium Griseummentioning
confidence: 99%
“…This previous proposal is also supported by the comparison with the avian medial pallium, showing the high similarity in terms of position and cytoarchitecture of reptilian MC and at least the avian ventral hippocampus. The fact that the latter expresses Prox1 is also a proof that a DG-like area was likely present in the medial pallium of stem amniotes [Abellán et al, 2014], instead of being a novel acquisition of mammals [Künzle, 2004;Striedter, 2016]. If confirmed that the MC of reptiles also expresses Prox1, this would also disagree with the proposal that this reptilian structure is comparable to the mammalian indusium griseum , as the latter does not express Prox1 [Abellán et al, 2014].…”
Section: Dg-like and Ca3-like Subdivisionsmentioning
confidence: 99%
“…In all mammals, it consists of identical, similarly convoluted and interlocked 3-layered subdivisions, which from medial to lateral are the dentate gyrus (DG), the hippocampus proper or Ammon's horns ( cornu ammonis or CA fields 1-3), and the subiculum (Sub) [Witter and Amaral, 2004;Hevner, 2016]. It is rostrally continuous with a narrow strip of gray matter called indusium griseum , which is sometimes considered a hippocampal vestige [Künzle, 2004;Laplante et al, 2013]. For details on the structure, connections, and function of the HF, the readers are also referred to other articles of this special issue [for instance, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In human brain, IG is found in the supracallosal gyrus and is made of a thin layer of gray matter. As a continuation of the hippocampus, it receives laminar-specific afferent inputs from the entorhinal cortex, the anterior and posterior piriform cortices, and the supramammillary region (Kunzle, 2004). This region was previously believed to be related to the olfactory system, but few studies have been reported.…”
Section: Discussionmentioning
confidence: 99%